Case studies in neurological rehabilitation - Gaber, Tarek A-Z. K. (Medicine, 2008)
Rehabilitation medicine is one of the fastest growing specialities in medicine. The largest sub-set of this field is neurological rehabilitation. This timely book, presented as a series of case studies, describes the wide range of clinical scenarios encountered by the rehabilitation medicine team and advises on management issues and options. Areas covered include ethical, medico-legal and social factors, touching on issues such as service organisation and patient reintegration. The book concludes with a set of multiple choice questions to test understanding and as the basis for preparation for professional examinations. This will be essential reading for all trainees in rehabilitation medicine, specialists from fields such as neurology where an understanding of the principles is important, and professionals from supportive allied health disciplines including physiotherapy, occupational therapy, speech therapy and nursing.